The prognostic significance of hTERT overexpression in cancers: A systematic review and meta-analysis. Issue 35 (August 2018) - Wang, Kai; Wang, Rui-Ling; Liu, Jian-Jun; Zhou, Ji; Li, Xue; Hu, Wen-Wei; Jiang, Wei-Jian; Hao, Ning-Bo
Abstract: Background: Human telomerase reverse transcriptase (hTERT) plays an important role in cancer progression. Recently, several clinical studies investigated how the overexpression of hTERT predicts the poor prognosis of solid tumors. However, the results were inconclusive, partly because of the small numbers of patients included. Method: We systematically searched PubMed, Web of Science, and Embase to identify relevant studies until August 2017. Hazard ratios (HRs) with 95% confidence intervals (CIs) were used to evaluate the association of hTERT expression and survival outcomes. Results: A total of 27studies enrolling 2530 solid tumor patients were included in this meta-analysis. There were strong significant associations between hTERT overexpression and all endpoints: overall survival (OS) (HR = 1.50, 95% CI: 1.31–1.73, P = .00), disease-free survival (HR = 1.84, 95% CI: 1.38–2.46; P = .00), and recurrence-free survival (HR = 1.79, 95% CI: 1.07–2.99; P = .028). In the subgroup analysis, it was found that the overexpression of hTERT induced poor OS in lung cancer (HR = 1.51, 95% CI: 1.21–1.89; P = .00). Conclusion: Our comprehensive systematic review concluded that the overexpression of hTERT was associated with poor survival in human solid tumors. hTERT may be a valuable predictive biomarker for prognosis.